2021
DOI: 10.3389/fmicb.2021.607512
|View full text |Cite
|
Sign up to set email alerts
|

A Virulence Associated Siderophore Importer Reduces Antimicrobial Susceptibility of Klebsiella pneumoniae

Abstract: The accessory genomes of many pathogenic bacteria include ABC transporters that scavenge metal by siderophore uptake and ABC transporters that contribute to antimicrobial resistance by multidrug efflux. There are mechanistic and recently recognized structural similarities between siderophore importer proteins and efflux pumps. Here we investigated the influence of siderophore importer YbtPQ on antimicrobial resistance of Klebsiella pneumoniae. YbtPQ is encoded in the yersiniabactin cluster in a prevalent mobil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The ABC transporters superfamily is among the largest and most broadly expressed protein superfamily, is found in all living organisms and is involved in almost every cellular, biological and physiological system ( Mercado-Lubo and McCormick, 2010 ). ABC transporters in the accessory genomes of bacterial pathogens significantly influence both virulence and antimicrobial resistance ( Theodoulou and Kerr, 2015 ; Farzand et al, 2021 ). There was a large number of differential metabolites between the two groups, of which seven belonged to the ABC transporters pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The ABC transporters superfamily is among the largest and most broadly expressed protein superfamily, is found in all living organisms and is involved in almost every cellular, biological and physiological system ( Mercado-Lubo and McCormick, 2010 ). ABC transporters in the accessory genomes of bacterial pathogens significantly influence both virulence and antimicrobial resistance ( Theodoulou and Kerr, 2015 ; Farzand et al, 2021 ). There was a large number of differential metabolites between the two groups, of which seven belonged to the ABC transporters pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the ABC transporter pathway implies that patients might be under toxic stress after exposure to SARS‐CoV‐2 34 . Besides, the accessory genomes of considerable pathogenic bacteria cover ABC transporters that contribute to antimicrobial resistance by multidrug efflux, 75 further explaining antibiotic resistance pathway enrichment. Sphingolipids are progressively recognized as critical mediators in participation with inflammatory responses and multiple pulmonary diseases 76 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, resistant strains produced more siderophores than their susceptible counterparts. Recently, it has been reported that the introduction of the mobile genetic element ICEKp from Klebsiella pneumoniae or a plasmid encoding YbtPQ (a siderophore importer encoded in the yersiniabactin cluster) reduced the susceptibility of E. coli to a wide range of antimicrobials ( Farzand et al, 2021 ). Regarding adhesins, type 1 fimbriae are the best known adhesive organelles among Enterobacteriaceae ( Abdelhalim et al, 2020 ) playing an important role in the initial steps of biofilm formation.…”
Section: Discussionmentioning
confidence: 99%